Follow-the-Sun is it really a strategy from the perspective of strategic management? - Serwiński, Marcin (Follow-the-Sun – czy to na pewno strategia z perspektywy zarządzania strategicznego?, 2021)
The article is a response to an issue, raised by Beulen (2012), related to time zone and strategy which have not been fused together in management or the outsourcing literature. “There has been some theoretical thinking on the impact of time zones on scheduling, but not on strategy” (Carmel, 2012, p. 2). The subject of the analysis is the Follow-the-Sun (FTS) strategy, which is the hardest among those taking advantage of time zone differences (cf. (Carmel & Espinosa, 2011, p. 58). The strategy’s main objective is to further increase the pace of R&D work by using project teams dispersed in distant time zones and therefore capable of ensuring a 24-hour work cycle without the need to work at night (Serwiński, 2019a, p. 1). In turn, the main goal of the paper is to present a specific proposal for classifying the FTS strategy in strategic management
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 138-149